A qualitative exploration of intentional nursing round models in the emergency department setting: investigating the barriers to their use and success. Issue 9 (16th March 2016) - Kirk, Kate; Kane, Ros
Abstract : Aims and objectives: This research aimed to investigate the use of intentional rounding within in the emergency department setting through exploration of the staff nurse experience. The focus was its implementation at a large teaching hospital in England. Background: Research into the use of intentional rounding in any area of practice is minimal in the UK; however, a broader evidence base comes from America. The majority of this research supports the notion of intentional rounding for improved patient care and outcomes. Research from the UK is generally more contested. There is less literature on using intentional rounding specifically in the emergency department setting. Design: Qualitative methodological approach. Methods: Semi‐structured interviews ( n  = 5) were completed with staff nurses working within an emergency department. A purposive sampling technique was used for recruitment. The data was then analysed using 'Framework Method of Qualitative Analysis' (Spencer et al . 2014). Results: The findings were categorised into four headings: (1) Improved patient experience, (2) Current unmanageability, (3) Adapting for the emergency department, (4) Benefits on achieving quality indicators and targets. Conclusion: The findings show that although staff felt the introduction of intentional rounding techniques could lead to improvements in patient safety and overall care experience, they also identified a range of difficulties and adaptations needed to ensure its success within this acute care environment. Relevance to clinical practice: The research offers an insight into the staff's perceptions of using intentional rounding and also explains the practical difficulties faced by the nursing staff with potential suggestions that may help to address these problems. Benefits include more open communication between staff and patients and potentially more timely response to patient need, which positively impacts levels of safety and satisfaction. Barriers include lack of staff engagement, and the environmental factors and pressures, within the ED setting.